Through a Random Route to the Goal: Theoretical Background and Application of the Method in Tourism Surveying in Poland - Sebastian Wójcik (Statistics in Transition New Series, 2020)
Classic survey methods are ineffective when surveying a small or rare population. Several methods have been developed to address this issue, but often without providing a full mathematical justification. In this paper we propose estimators of parameters relating to Random Route Sampling and explore their basic properties. A formula for the Horvitz-Thompson estimator weights is presented. Finally, a case of a tourism-related survey conducted in Poland is discussed.
Keywords: 519; random route; Horvitz-Thompson estimator